Selected aspects of participation of a community organization in proceedings concerning individual cases of students and postgraduates - Dańczak, Paweł (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The purpose of this paper is to present an in-depth analysis of the participation of a community organization in administrative proceedings concerned with students and postgraduates’ matters. Deliberations conducted in this paper have been limited to strictly selected and described in its content entities. Their selection was determined by the specificity of student-postgraduate affairs and the whole sphere of higher education. This includes an explanation of the legal nature of those entities, their procedural rights, which have their origin in the regulations of the administrative procedure which in these particular categories of cases will apply mutatis mutandis.